The education of patients in prandial insulin dosing related to the structure of bolus calculators - Marlena Błazik; Ewa Pańkowska (Pediatric Endocrinology, Diabetes and Metabolism)
The metabolic effect of insulin pump therapy depends on precise adjustments of insulin to food intake ratio. Calculation of prandial insulin dose is a complex process employing many variant factors such as pre-prandial glucose and carbohydrate (CHO) levels, glucose index, insulin to CHO ratio (ICR) and active insulin. Bolus calculators are very effective in controlling blood glucose level in patients treated with continuous subcutaneous insulin infusion (CSII). Most of modern bolus calculators are built into the insulin pump unit and are only accessible to pump users. In addition, some models offer nutrition database. Patients? education is an essential step in proper interpretation and application of bolus calculators? various algorithms.